IMPROVING CRITICAL THINKING ABILITY AND MATHEMATICAL DISPOSITION OF HIGH SCHOOL STUDENTS THROUGH INTEGRATED SAINTIFIC APPROACH TO BRAIN BASED LEARNING - Enen Nurbaeti; Meida Sugiharti (IKIP Siliwangi, 2019)
The purpose of this study was to examine the problem of achievement and improved critical thinking skills and dispositions mathematical high school students between those who use the scientific approach to integrating brain based learning with a scientific approach , examining the association between variablesand an overview of student performance. This study is an experimental study with a design pretest-posttest design. Sampling in this study using purposive sampling technique . The instruments used were tests and non-tests , the test instruments included tests of mathematical critical thinking skills while the non-test included attitude scale tests Student mathematical disposition . The results showed that the achievement and improvement of critical thinking skills (CTS) with a scientific approach to integrating Brain-based Learning (SAIBBL) better than class with scientific approach (SA). Mathematical Disposition (MD) student in the classroom with using learning (SAIBBL) better than students in class with SA. There is a strong association between CTS and MD . The overall picture of student performance with SAIBBL is superior and students are more active in learning. These results prove that the use of SAIBBL is better than SAI.